SOME ISSUSES OF CORRELATION OF TOURISM PRODUCT AND THE PACKAGE TOUR - Saghoyan, Eva (State and Law, 2023)
The article discusses some issues of the essence and correlation of tourism product and the package tour. The author indicates collisions between provisions of the Law of RA on ''Tourism and tourism activities” concerning an object of contractual relationship between tour operator/agent and consumer. In order to ensure also the legal regulation of packages, formed in accordance with the order of the consumer and the aim of trip, the author suggests not to limit the consistency of packages and the minimal duration of tourist services.
Keywords: tourism product; package tour; contract; tourism services